Visualizing Neuropharmacological Effects of Guanfacine Extended Release in Attention Deficit Hyperactivity Disorder Using Functional Near-Infrared Spectroscopy - Ikeda, Takahiro; Inoue, Akari; Tanaka, Daisuke; Hashimoto, Tamao; Sutoko, Stephanie; Tokuda, Tatsuya; Kyutoku, Yasushi; Maki, Atsushi; Yamagata, Takanori; Dan, Ippeita; Monden, Yukifumi (Frontiers in Neuroergonomics, 2021)
Objective: In the current study, we explored the neural substrate for acute effects of guanfacine extended release (GXR) on inhibitory control in school-aged children with attention deficit hyperactivity disorder (ADHD) using functional near-infrared spectroscopy (fNIRS). Methods: Following a GXR washout period, twelve ADHD children (6–10 years old) performed a go/no-go task before and 3 hours after GXR or placebo administration, in a randomized, double-blind, placebo-controlled, crossover design study. In the primary analysis, fNIRS was used to monitor the right prefrontal cortical hemodynamics of the participants, where our former studies showed consistent dysfunction and Osmotic release oral system-methylphenidate (OROS-MPH) and atomoxetine hydrochloride (ATX) elicited recovery. We examined the inter-medication contrast comparing the effect of GXR against the placebo. In the exploratory analysis, we explored neural responses in regions other than the right prefrontal cortex (PFC). Results: In the primary analysis, there was no significant change in neural responses in the right PFC for inter-medication (one sample t-test, n.s., Cohen’s d=0.01). However, in the post hoc analysis, we observed significant change in the oxy-Hb signal in the right angular gyrus (AG) for inter-medication (one sample t-test, p<.05, uncorrected, Cohen’s d=0.71). Conclusions: These results are different from the neuropharmacological effects of OROS-MPH and ATX, which up-regulate reduced right PFC function in ADHD children during inhibitory tasks. This analysis, while limited by its secondary nature, suggests that the improved cognitive performance was associated with activation in the right AG, which might serve as a biological marker to monitor the effect of GXR in ADHD children.